Development of a screening instrument to assess breastfeeding in the first 48 hours - Anny Cristine de Araújo; Amanda de Conceição Leão Mendes; Gabrielle Mahara Martins Azevedo Castro; Natalia Carlos Maia Amorim; Priscila Pereira Machado Guimarães; Ruty Eulália de Medeiros Eufrásio; Savio Marcelino Gomes; Thaiz Mattos Sureira (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: develop a screening tool (AMA-48) to assess the risk of the mother-baby dyad not progressing positively in exclusive breastfeeding within the first 48 hours of hospital admission. Methods: this methodological study was carried out in a child-friendly hospital located in the interior of the Northeast Region of Brazil, between July2019 and August 2020. The study followed the following phases: 1) search in the literature to reformulate the construct; 2) restructuring of the construct and instrument; 3) content validation through evaluation by a committee of experts. Outcomes: the literature search resulted in the selection of ten documents. From these, the objective and structure of the instrument were defined, generating a structured questionnaire (11 items). Twenty-two experts considered 64% of the items “adequate”. After reformulating and reevaluating the instrument, it was considered objective (85%), clear (90%) and relevant (95%). In the end, the instrument obtained a satisfactory overall average Content Validity Index of0.88 (0.05) and included variables related to the unfeasibility of exclusive breastfeeding, maternal and neonatal anthropometry and breastfeeding difficulties, classifying the dyad at usual, medium and high risk. Conclusion: a tool with content validity was obtained, developed for low complexity services, which indicates the risk of the dyad not continuing exclusive breastfeeding.